Efficacy of Intraoperative Recurrent Laryngeal Nerve Monitoring During Thoracoscopic Esophagectomy for Esophageal Cancer: A Systematic Review and Meta-Analysis - Wang, Xinxin; Guo, Haixie; Hu, Quanteng; Ying, Yongquan; Chen, Baofu (Frontiers in Surgery, 2021)
Background: Recurrent laryngeal nerve paralysis (RLNP), a severe complication of mini-invasive esophagectomy, usually occurs during lymphadenectomy adjacent to recurrent laryngeal nerve. This systematic review and meta-analysis aimed to evaluate the efficacy of intraoperative nerve monitoring (IONM) in reducing RLNP incidence during mini-invasive esophagectomy. Methods: Systematic literature search of PubMed, EMBASE, EBSCO, Web of Knowledge, and Cochrane Library until June 4, 2021 was performed using the terms “(nerve monitoring) OR neuromonitoring OR neural monitoring OR recurrent laryngeal nerve AND (esophagectomy OR esophageal).” Primary outcome was postoperative RLNP incidence. Secondary outcomes were sensitivity, specificity, and positive and negative predictive values for IONM; complications after esophagectomy; number of dissected lymph nodes; operation time; and length of hospital stay. Results: Among 2,330 studies, five studies comprising 509 patients were eligible for final analysis. The RLNP incidence was significantly lower (odds ratio [OR] 0.33, 95% confidence interval [CI] 0.12–0.88, p < 0.05), the number of dissected mediastinal lymph nodes was significantly higher (mean difference 4.30, 95%CI 2.75–5.85, p < 0.001), and the rate of hoarseness was significantly lower (OR 0.14, 95%CI 0.03–0.63, p = 0.01) in the IONM group than in the non-IONM group. The rates of aspiration (OR 0.31, 95%CI 0.06–1.64, p = 0.17), pneumonia (OR 1.08, 95%CI 0.70–1.67, p = 0.71), and operation time (mean difference 7.68, 95%CI −23.60–38.95, p = 0.63) were not significantly different between the two groups. The mean sensitivity, specificity, and positive and negative predictive values for IONM were 53.2% (0–66.7%), 93.7% (54.8–100%), 71.4% (0–100%), and 87.1% (68.0–96.6%), respectively. Conclusion: IONM was a feasible and effective approach to minimize RLNP, improve lymphadenectomy, and reduce hoarseness after thoracoscopic esophagectomy for esophageal cancer, although IONM did not provide significant benefit in reducing aspiration, pneumonia, operation time, and length of hospital stay.